Implementation of Imagery Training in Increasing parking and Gate-in Shooting Performance of Musi Rawas Woodball - Dini Mayang Dini; Wawan Syafutra (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
Theref ore this study aims to determine Imagery Training to improve the results of Musi Rawas Parking and Gate-in Woodball strokes. This research is an experi mental research in the form of one-group pretest-posttest design, the sample of this research is 10 athletes and then given treatment in the form of imagery training exercises. The instrument used was the parking and gate-in skill test for the woodball athlete Musi Rawas. The data analysis technique used was SPSS 22 the Paired Sample t-test. The results of this study there is a significant increase with the test criteria α = 0.05, then the T table is 1.833 and the Tcount is 9.000. From the results of this study indicate that Ha: accepted and Ho: rejected because in accordance with the rules of hypothesis testing decisions. According to Priyastama (2017: 91) which states the significance value obtained (p) <0.05 then Ho is rejected, and Ha is accepted or Ha is accepted if if Tcount <Ttable and the significance value obtained (p)> 0.05 then Ha is rejected and Ho is accepted or Ho is accepted if Thitung> Ttabel. Based on the results of paired samples test, the SPSS output obtained the sig value. (p) 0.000 <from 0.05 and the value of tcount (9.000)> t table (1.833). The results above show that Ha: accepted and Ho: rejected. If Ha is accepted, then Ha's statement reads "Imagery Training there is an increase in the results of Parking and Gate-in Athletes Beginner Woodball Musi Rawas".Key words:  Woodball, imagery training, parking stroke and gate-in